Comparative analysis of Cedar virus entry and antiviral innate immune responses in human, porcine, and fruit bat cell culture systems - Lenhard, Lea; Justus Liebig University Giessen (My University, 2026)
Henipaviruses, such as Hendra virus (HeV) and Nipah virus (NiV), are emerging threats to global public health and are currently listed on the WHO Blueprint list of epidemic threats, which require immediate research and development efforts. Their high pathogenicity and ability to inhibit the host’s innate immune response complicate research into antiviral drugs and vaccines. The discovery and isolation of the first non-pathogenic henipavirus, Cedar virus (CedV), from black flying foxes in Australia has created new possibilities for henipavirus research under low biosafety conditions. Although CedV’s low virulence has been demonstrated in animal trials and some cell culture experiments, the mechanisms by which CedV enters the cells of its natural host, fruit bats, and whether such infection activates innate immune responses and cellular stress remain poorly understood. This project sheds light on the receptors used by CedV to enter the cells of Egyptian rousette bats, as well as the innate immune processes and cytopathic effects that follow the infection of different epithelial cell lines.
Keywords: immunology; bat; Rousettus aegyptiacus; cellular stress; viral entry; ephrin; henipavirus; Cedar virus; ddc:630